(untitled) (ACTA MEDICA PERUANA, 2024)
It has been studied five cases of P.N.H. In four of them the disease presented in its classical form; one of them showed more PNH "defect" than disease. In all our patients at the time of diagnosis was found anemia; in three leukopenia and in two thrombocytopenia. None of them was treated with iron; three patients were treated with androgens beings only one of them benefited. Two patients were given adrenal steroids without any evidence of improvement.